Integrating phase field and crystal plasticity finite element models for simulations of titanium alloy Ti-5553. (7th September 2021) - Agius, Dylan; O'Toole, Patrick; Wallbrink, Chris; Sterjovski, Zoran; Wang, Chun-Hui; Schaffer, G B
Abstract: The ability to simultaneously predict the microstructure and bulk material properties of 3D printed (additively manufactured or AM) metals is critical to the development of process intelligence that can be used by a digital-twin for forecasting and optimising alloy composition and fabrication parameters. This study proposes a simulation framework for predicting the microstructure and corresponding meso- and macro-scale properties of AM materials. This is achieved by integrating phase-field and crystal plasticity modelling techniques, whereby the phase field model predicts the microstructure and the crystal plasticity constitutive model computes the stress–strain evolution using the microstructure as the input. The simulation of multiple microstructures demonstrates that this integrated approach can be used to test the influence of different microstructures on the mechanical properties of titanium alloy Ti-5553. This includes the influence of grain size and grain orientation on both the meso- and macro-scale behaviour.